2010
DOI: 10.1371/journal.pone.0009084
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gene Expression in Hepatic Cells by the Mammalian Target of Rapamycin (mTOR)

Abstract: BackgroundWe investigated mTOR regulation of gene expression by studying rapamycin effect in two hepatic cell lines, the non-tumorigenic WB-F344 cells and the tumorigenic WB311 cells. The latter are resistant to the growth inhibitory effects of rapamycin, thus providing us with an opportunity to study the gene expression effects of rapamycin without confounding effects on cell proliferation.Methodology/Principal FindingsThe hepatic cells were exposed to rapamycin for 24 hr. Microarray analysis on total RNA pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
1
17
1
Order By: Relevance
“…These findings are in keeping with our previous studies on a panel of hepatic cell lines in which we showed that effects of rapamycin on gene expression disproportionately affected genes whose promoter regions contained E-boxes (19). Although this indicated the possibility of a transcriptional control mechanism involving c-Myc, we went on to show that the rapamycin-induced effects were independent of c-Myc.…”
Section: R29 Regulation Of Hepatic Translation By Mtorsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in keeping with our previous studies on a panel of hepatic cell lines in which we showed that effects of rapamycin on gene expression disproportionately affected genes whose promoter regions contained E-boxes (19). Although this indicated the possibility of a transcriptional control mechanism involving c-Myc, we went on to show that the rapamycin-induced effects were independent of c-Myc.…”
Section: R29 Regulation Of Hepatic Translation By Mtorsupporting
confidence: 90%
“…The results of our studies indicated resistance to the growth inhibitory effect of rapamycin at the level of G1 cell-cycle progression (13) and translation of 5=TOP mRNAs (12,14). We have also had a long-standing interest in the regulation of hepatic gene expression by mTOR (13,19,21). In the present study, we have extended these observations by characterizing the effect of rapamycin on the hepatic transcriptome and translatome in the late gestation fetal rat and in the adult rat.…”
mentioning
confidence: 60%
“…53 Our initial studies focused on the WB-F344 and WB311 cell lines. One goal of these studies was to identify rapamycin-induced and rapamycin-suppressed ) and total ribosomal protein S6.…”
Section: Mtorc1-mediated Regulation Of Gene Expressionmentioning
confidence: 99%
“…Roughly equivalent numbers of genes were upregulated and downregulated in response to rapamycin (60 downregulated, 66 upregulated), a finding that recapitulated our earlier results in hepatic cell lines. 33,53 In order to characterize the effects of rapamycin on gene expression in fetal liver, results were analyzed using two separate instruments, Gene Set Enrichment Analysis (GSEA), 57,58 and Ingenuity Pathways Analysis (IPA; Ingenuity ® Systems, www.ingenuity.com). Results using GSEA did not disclose a significant overrepresentation of any transcription factor binding domains.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…In addition, microarray analyses testing the extent of global alterations in the transcriptome in yeast and in mammals contribute to the understanding of the mechanisms and pathways associated with the effect of rapamycin (7)(8)(9)(10)(11)(12). In vivo studies indicate that rapamycin results in developmental delay in different organisms including Drosophila melanogaster, zebrafish and mice (6,13,14).…”
Section: Introductionmentioning
confidence: 99%